Proteomic analysis of rat plasma following transient focal cerebral ischemia. (December 2011) - Chen, Ruoli; Vendrell, Iolanda; Chen, Carl PC; Cash, Diana; O''Toole, Kim Galley; Williams, Steve A; Jones, Christopher; Preston, Jane E; Wheeler, Jun X
Aim: This study aimed to identify plasma protein changes in a rat model of ischemic stroke using a proteomic approach.Materials & Methods: Four male Sprague–Dawley rats (3–6 months old) were subjected to 90 min of left middle cerebral artery occlusion under anesthesia with 1.5% isoflurane in O2 /air followed by 24-h reperfusion. Blood samples (∼100 µl) were collected at baseline, at the end of 90-min middle cerebral artery occlusion and at 24-h postreperfusion. Brain injuries were assessed by MRI at 24-h postreperfusion. Quantitative comparison of global plasma protein expression was performed using 2D differential in-gel electrophoresis. Differentially expressed protein spots were identified using peptide sequencing tandem mass spectrometry.Results: These rats had clear brain infarction in the left hemisphere detected by MRI. Thirty-three protein spots of plasma samples were differentially expressed following focal cerebral ischemia/reperfusion. These protein spots belonged to eight proteins. Six of them (α2-macroglobulin, complement C3, inter-α- trypsin inhibitor heavy chain H3, serum albumin, haptoglobin and transthyretin), which are a class of acute-phase proteins, changed significantly.Conclusion: This study describes the responses of young rats to focal cerebral ischemia and suggests that future studies should use aged animals to better mimic the clinical ischemic stroke setting.